Non-woody Biomass as Sources of Nanocellulose Particles: A Review of Extraction Procedures - Owonubi, Shesan J.; Agwuncha, Stephen C.; Malima, Nyemaga M.; Shombe, Ginena B.; Makhatha, Elizabeth M.; Revaprasadu, Neerish (Frontiers in Energy Research, 2021)
Nanocellulose has been reported to be a very useful biomaterial with applications in biomedical, pharmaceutical, built industry, automobile, aerospace and many more. Its advantages over synthetic fibers include renewability, energy efficiency, cost effectiveness, biodegradability and good mechanical and thermal properties. However, the production of cellulose nanoparticles (CNPs) has focused more on woody plant sources. Non-woody biomass constitutes a large group of plant sources that are yet to be given the proper attention for utilization as raw material for nanocellulose particle production. This group of lignocellulosic biomasses is generally obtained as waste from farming activities, home gardens or office wastes. They are majorly composed of cellulose, hemicellulose, and lignin. However, their composition varies widely from one plant source to another. The variation in their composition results in limitations in the procedures employed in extraction of CNPs and of processing of the extracted CNPs. This means that different biomasses may have different ways by which CNPs are extracted from them. Therefore, this review intends to x-ray these variations, its effect on the structural properties of extracted CNPs and possible ways such limitations can be mitigated.